Antibacterial Activity and Phytochemical Screening of Methanol Extract of Rambai (Baccaurea motleyana Muell. Arg.) Leaves from the Tropical Rainforest of East Kalimantan - Widayat, Wahyu; Indriyanti, Niken; Adestia, Talita Shofa; Wibowo, Ekasari Kartika Putri (Kimia Padjadjaran, 2024)
Antibiotic resistance is a problem in the health field. Potential sources of raw materials are needed to overcome this problem. Rambai (Baccaurea motleyana Muell. Arg.) is one of the Baccaurea genus which is widespread throughout Asia. Several species of Baccaurea are known for their antimicrobial properties. Extraction was performed using the maceration method with methanol as solvent. Phytochemical screening of the extract was analyzed using a standard method. The antibacterial activity was tested using the agar diffusion method (Kirby-Bauer) with extract concentrations of 2, 4, 6, 8, and 10 mg/disc. The test bacteria used were Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. The results showed that the extract contained alkaloids, phenolics, and flavonoids. B. motleyana methanol extract showed antibacterial activity at a concentration of 10 mg/disc, with an inhibition zone of 11 mm. Based on these results, B. motleyana leaves have potential as an antibacterial agent.